计算两函数积的高阶导数——广义莱布尼茨公式



广义莱布尼茨公式

\begin{equation*} [f(x) \cdot g(x)] ^{(n)} = \sum _{k = 0} ^{n} C _{n} ^{k} f ^{(k)} (x) g^{(n - k)} (x) = \sum _{k = 0} ^{n} \frac{n!}{k!(n-k)!} f ^{(k)} (x) g^{(n - k)} (x) \end{equation*}

其中令$f^{(0)}(x)=f(x)$。

用归纳法证明如下:

$n=1$ 时,显然成立。

设$n=m$时成立,则$n=m+1$时

\begin{equation*} \begin{split} [f(x) \cdot g(x)] ^{(m + 1)} =& \{ [f(x) \cdot g(x)] ^{(m)} \} ' \\ =& [\sum _{k = 0} ^{m} C _{m} ^{k} f ^{(k)} (x) g^{(m - k)} (x)]'= \sum _{k = 0} ^{m} C _{m} ^{k} [f ^{(k)} (x) g^{(m - k)} (x)]' \\ =& \sum _{k = 0} ^{m} C _{m} ^{k} [f ^{(k + 1)} (x) g^{(m - k)} (x) + f ^{(k)} (x) g^{(m + 1 - k)} (x)]\\ =& \sum _{k = 0} ^{m} C _{m} ^{k} f ^{(k + 1)} (x) g^{(m - k)} (x) + \sum _{k = 0} ^{m} C _{m} ^{k} f ^{(k)} (x) g^{(m + 1 - k)} (x)\\ =& \sum _{k = 1} ^{m + 1} C _{m} ^{k - 1} f ^{(k)} (x) g ^{(m + 1 - k)} (x) + \sum _{k = 0} ^{m} C _{m} ^{k} f ^{(k)} (x) g^{(m + 1 - k)} (x)\\ =& f^{(m + 1)}(x)g(x) + \sum _{k = 1} ^{m} (C _{m} ^{k - 1} + C _{m} ^{k}) f ^{(k)} (x) g ^{(m + 1 - k)} (x) + f(x)g ^{(m + 1)}(x)\\ =& f^{(m + 1)}(x)g(x) + \sum _{k = 1} ^{m} C _{m + 1} ^{k} f ^{(k)} (x) g ^{(m + 1 - k)} (x) + f(x)g ^{(m + 1)}(x)\\ =& \sum _{k = 0} ^{m + 1 } C _{m + 1} ^{k} f ^{(k)} (x) g ^{(m + 1 - k)} (x) \end{split} \end{equation*}

得证。

特例,当 $n=2$时,

\begin{equation*} [f(x) \cdot g(x)] '' = fg''+2f'g'+f''g \end{equation*}

当 $n=3$时,

\begin{equation*} [f(x) \cdot g(x)] ''' = fg'''+3f'g''+3f''g'+f'''g \end{equation*}

标签: 导数, 莱布尼茨公式

添加新评论

captcha
请输入验证码